Some Issues on the Development of the Armenian Terms Vocabulary - Telyan, Leonid (Bulletin of Yerevan University B: Philology, 2021)
At the present stage, the improvement of the Armenian terminological vocabulary takes place mainly due to its rich intra-linguistic potential. The article also discusses the activities of a number of institutions and specialists aimed at the realization of the term building means both in Eastern Armenian and Western Armenian.
Keywords: terminology; term buildingy; vocabulary; borrowing; Eastern Armenian; Western Armenian